2020
DOI: 10.1001/jamaneurol.2019.4284
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cognitive and Behavioral Features Between Adults With Tuberous Sclerosis and Frontotemporal Dementia

Abstract: IMPORTANCE Individuals with tuberous sclerosis complex can develop a progressive neuropsychiatric syndrome known as tuberous sclerosis-associated neuropsychiatric disorders. Tuberous sclerosis-associated neuropsychiatric disorders symptoms overlap with clinical criteria for frontotemporal dementia, yet the association between the 2 has not been explored.OBJECTIVE To investigate the potential association between tuberous sclerosis-associated neuropsychiatric disorders and frontotemporal dementia. DESIGN, SETTIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…1C ). These results suggest that, similar to our earlier reports ( 11, 15 ), genetic variants that decrease levels of TSC1/hamartin are associated with tauopathy.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…1C ). These results suggest that, similar to our earlier reports ( 11, 15 ), genetic variants that decrease levels of TSC1/hamartin are associated with tauopathy.…”
Section: Resultssupporting
confidence: 91%
“…In earlier clinical-translational studies, we have shown a linkage between TSC1 gene and agerelated tauopathies (11,15). With this study, we establish the mechanistic basis for this linkage, adding TSC1 to a set of genes including glucocerebrosidase A (GBA), progranulin (PGRN) and cathepsin D (CTSD) in which pathogenic variants are associated with both childhood developmental and age-associated neurodegenerative diseases (7,8,53).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations